THE APPLICATION OF TROPICAL ARCHITECTURE CONCEPT AT BUILDING OF SMP ALAM LEBAH PUTIH SALATIGA - Dea Sekar; Gunawan Gunawan; Sri Yuliani (Universitas Sebelas Maret Surakarta, 2018)
The school of nature is an educational model that utilizes nature's potential as the main learning method. Therefore, to realize a natural school that can pay attention to the surrounding natural conditions, then selected using the principle design of tropical architecture. The application of the concept of tropical architecture to the building of SMP Alam Lebah Putih aims to support natural-based learning method and to exploit local climate potential, that is tropical climate. The research method used is applied research, through the exploration of ideas and data collection which then concluded and become the guidance in the design analysis. The application of the principle of tropical architecture in the building of SMP Alam Lebah Putih, based on the analysis that is set on the mass building, the building mass, the orientation of the building, and the material applied.